Non-traditional training in youth soccer players: Effects on agility and on sprint performance - Carvutto, R.; Damasco, C.; De Candia, M. (Journal of Human Sport & Exercise, 2021)
Soccer is a high-intensity activity requiring several physical and technical components such as agility, speed, strength, and power production. High-intensity functional training (HIFT) is a relatively new training modality that emphasizes functional, multi-joint movements that elicit greater muscle recruitment with respect to more traditional exercises. The aim of the study was to verify the effects of 8 weeks of non-traditional training, specifically HIFT, on agility and sprint performance in young soccer players. Twenty-eight male subjects (M age 12.6 ± SD 0.5 years) were divided into an experimental group that performed the HIFT (NTT, n = 14) and in a control group (TT, n = 14) that followed a traditional training. HIFT included functional exercises, High-Intensity Interval Training (HIIT), technical exercises, agility, and change of direction ability. Twenty meters sprint test and 21-m agility test were administered to assess sprint performance and agility, respectively. After 8 weeks of training a significant interaction Group x Time (p < .01) was found for NTT for agility and a non-significant improvement in relation to sprint performance (p > .05). No differences were detected in the TT. An 8-week NTT based on HIFT can represent an innovative and additional methodology to improve the agility performance of young soccer players.